Determining risk factors of cardiovascular diseases using multiple logistic regression analysis case study: Komfo Anokye Teaching Hospital (2011-2012) - Opoku, Emmanuel Kwasi (2016)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the Degree of Master of Science in Industrial Mathematics.